Students’ Difficulties in Interpreting Message of Listening Comprehension - Ari Saputra; Lalu Arwan Darmajaya; Rudi Anggara Riantara (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2021)
This research aimed at finding how does the student’s difficulties in interpreting the message of the listening comprehension, and to know the factors causes of students’ difficulties in interpreting message of listening comprehension for the eleventh-grade students of Madrasah Aliyah Mardhatillah NW Penakak in the school year 2020/2021. The sample of this research was the Eleventh-Grade students of Madrasah Aliyah Mardhatillah NW Penakak. The number of population was 29 students. This research was using qualitative descriptive. The data was gathered by interview, observation and documentation. The result of this research was the Eleventh-Grade students of Madrasah Aliyah Mardhatillah NW Penakak difficult to interpreted message of listening comprehension. It was based on three factors influencing their listening were listening material, listener factor, and physical environment. Therefore, accents, pronunciation, speed of speech, insufficient of vocabulary, different accents of the speaker, lack of concentration were major problems encountered by the Eleventh-Grade students of Madrasah Aliyah Mardhatillah NW Penakak.